Functional miR-142a-3p Induces Apoptosis and Macrophage Polarization by Targeting tnfaip2 and glut3 in Grass Carp (Ctenopharyngodon idella) - Tao, Lizhu; Pang, Yifan; Wang, Anqi; Li, Lisen; Shen, Yubang; Xu, Xiaoyan; Li, Jiale (Frontiers in Immunology, 2021)
In the process of microbial invasion, the inflammation reaction is induced to eliminate the pathogen. However, un-controlled or un-resolved inflammation can lead to tissue damage and death of the host. MicroRNAs (miRNAs) are the signaling regulators that prevent the uncontrolled progress of an inflammatory response. Our previous work strongly indicated that miR-142a-3p is related to the immune regulation in grass carp. In the present study, we found that the expression of miR-142a-3p was down-regulated after infection by Aeromonas hydrophila. tnfaip2 and glut3 were confirmed as be the target genes of miR-142a-3p, which were confirmed by expression correlation analysis, gene overexpression, and dual luciferase reporter assay. The miR-142a-3p can reduce cell viability and stimulate cell apoptosis by targeting tnfaip2 and glut3. In addition, miR-142a-3p also regulates macrophage polarization induced by A. hydrophila. Our results suggest that miR-142a-3p has multiple functions in host antibacterial immune response. Our research provides further understanding of the molecular mechanisms between miRNAs and their target genes, and provides a new insights for the development of pro-resolution strategies for the treatment of complex inflammatory diseases in fish.